IMPLEMENTATION OF SADD AL-DZARI'AH IN MARRIAGE ANNULMENT DUE TO RELATIONAL STATUS MANIPULATION (A STUDY OF CIBINONG RELIGIOUS COURT DECISION 4188/PDT.G/2023/PA.CBN) - Helmi Zainu Al Abbad; Emha Hasan Nashrulloh Asy'ari (Program Pascasarjana UIN Sumatera Utara, 2026)
This study analyzes the ratio decidendi in Cibinong Religious Court Decision Number 4188/Pdt.G/2023/PA.Cbn on marriage annulment due to premarital relational status manipulation, using Sadd al-Dzari’ah as an interpretative framework. The case is significant because Indonesian law does not expressly recognize concealed relational status as a ground for annulment, although maintaining a marriage founded on dishonesty may generate mafsadah. This normative legal research uses case, statutory, and conceptual approaches, with legal materials collected through library research and analyzed qualitatively-normatively. The findings show that the panel annulled the marriage based on facts indicating the Respondent’s bad faith and linked them to Article 27(2) of the Marriage Law in conjunction with Article 72(2) of the Compilation of Islamic Law. Analytically, relational status manipulation was the initial cause, while maintaining the dishonesty-based marriage constituted dzari’ah ghalibah. The identified mafsadah comprised a strongly presumed risk of adultery and damage to the marriage contract’s integrity caused by ghurūr. Annulment before consummation (qabla dukhul) therefore served corrective and preventive functions, confirming the complementarity of positive law and Sadd al-Dzari’ah. Practically, the findings offer Religious Court judges a preventive assessment framework for assessing concealed facts, intent, evidence, and potential mafsadah in cases without replacing formal legal grounds.